Development of Ms Access 97 Based Wildlife Database: Aves and Mammalia of Malaysia - Mohammad Afandi, Syamsul Herman (2000)
Development of databases has become a major activity in computer industry. Database plays significant role in many fields which slowly has its impact on wildlife management. With a reliable database, storage of information on wildlife is proper, safe and well managed. The main objective of the study is to develop a computerized database on wildlife in Malaysia. The database contained 966 species which included 320 species of mammals and 646 species of birds in Malaysia. Both primary data and secondary data were compiled in the database. Important components used in the database are such as scientific name, local name, common English name, order, family, grouping, brief description, photo, status, protection feeding structures and habitat of the wildlife. Designing the database comprised of three major phases; data collection, data design and system design. In data design, an Entity Relationship model was designed to describe entities, relationship and attributes of the 'Wildlife Database'. Four entities were identified namely Wildlife, Habitat, Feeding Structure and Protection. In the system design phase, major designing works were concentrated on data flow, menu system, form design and graphical user interface. Selected software was Microsoft Access 97 as the storage and application software. Upon completion, the database run on PC with at least Pentium 100 Mhz, 64 MB RAM Memory, CD ROM 20 X and VGA Card. It is necessary to have Microsoft Windows 95 and Microsoft Access 97 to run the application. The need for researchers, students, lecturers or even normal user to retrieve valuable information on wildlife quickly and accurately can be achieved through this project Futhermore, with the development of the 'Wildlife Database of Malaysia', it is hoped that it will facilitate the management of wildlife in Malaysia or even in neighbouring countries.